Palladium on iron oxide nanoparticles: the morphological effect of the support in glycerol hydrogenolysis - Ge, J; Zeng, Z; Liao, F; Zheng, W; Hong, X; Tsang, S (2013)
Palladium supported on different shaped iron oxides has been synthesized and tested in glycerol hydrogenolysis in order to investigate the morphological effect of the support on catalytic performance. The plate-like iron oxide support exhibits a much higher activity due to the presence of more basic sites (oxygen vacancies) on its predominant polar surface. Thus, by tailoring the shape of the crystallized support, we show that bifunctional metal-oxide catalysis at the interface, like in the present example, can be significantly manipulated. © 2013 The Royal Society of Chemistry.